Development and evaluation of a deep knowledge and skills based assignment: Using MRI safety as an example. Issue 4 (November 2018) - Warren-Forward, H.M.; Kalthoff, O.
Abstract: Introduction: Using magnetic resonance imaging (MRI) safety as an example, this paper discusses the development of an innovative multiple-step assignment task designed to increase student engagement and learning of important concepts. The paper also summarises student feedback about the assessment as well as thematic analysis of categories thought important to students. Method: A multi-step assignment was designed. Step one was the reading of a MRI safety article, step two was the construction and submission of 5 short answer questions believed to be important concepts of understanding and step three was the answering of 15 questions compiled from all student questions by the course coordinator. The motivation to answer the course coordinator compiled questions was the knowledge that five of these questions would be in the end of course examination. At the completion of the assignment, students were asked to complete an anonymous on-line questionnaire about the assignment task. Thematic analysis was used to gather data on what students perceived to be the most and least important concepts in the article. Results: All students replying to the survey stated that they understood why MRI safety is an important topic and 79% reported this assignment was both a positive learning experience and provided understanding of the topic. Only 18% of students believed that they would have learned more through a formal lecture. Conclusion: The design of this assignment task can be used in any course, not just in medical radiation science, where student learning and understanding is critical. Highlights: Responding to concerns of clinical partners on student knowledge of MRI safety. A proffered model for better engagement of students in the assessment process. Enabled students to appreciate the important information in literature. Developing the skills of lifelong learning. Potentially enabled students to develop a deeper understanding of MRI safety.